Economic and Integration cooperation of the Turkic-Speaking Republics (Journal of Oriental Studies, 2017)
The Central Asian region is one of the subjects studied in international relations. This region corresponds to the geographical location of the post-Soviet Turkic-speaking republics. In this article, we pay special attention to the Central Asian region, as the whole of Central Asia, a Turkic-speaking region with the exception of Tajikistan. The main problems of each separate Turkic country are similar or even identical, so it is time to pay special attention to strategies aimed at the convergence of these countries. The article examines the region of the Turkic-speaking republics in the process of regionalization, as an example of the union, to work closely with neighboring countries in the field of economics and participating in integration projects.